Brake Strategy Analysis for Industrial Normal-closed Brake Based on Rotational Inertia Test and Simulation - Sun, Yuantao; Chen, Kaige; Zhang, Qing; Qin, Xianrong; Zhang, Jianjie (Journal of Engineering and Technological Sciences, 2019)
Industrial brakes pose the dilemma of weighing brake capability against brake impact since the brake torque cannot be adjusted. On the one hand, the brake torque may be insufficient to stop the movement within a limited distance or parking position. On the other hand, the brake torque may be so high it can damage the transmission chain. In this study, the traditional brake strategy and the field oriented control (FOC) brake strategy were compared through simulation and a rotational inertia test. The influence of the rated brake torque and the open-closed ratio were obtained. Based on the test and simulation results, a semi-empirical formula that defines the relationship between relative brake capability and open-closed ratio was developed. Additional simulations were performed to analyze the performance of the brake in a flexible transmission chain. As an industrial application example, the benefits and the cost of a ?smart brake? based on the FOC brake strategy were analyzed. The results indicate that the equivalent brake torque with the FOC brake strategy is a function of the real-time controllable input and open-closed ratio, which can be conducted during the braking procedure. This can be an efficient way to solve the above problems.